2014
DOI: 10.4025/reveducfis.v25i2.21685
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficácia Esportiva: uma revisão sistemática dos instrumentos de medida

Abstract: RESUMOO papel da autoeficácia no desempenho é foco de estudo no âmbito esportivo. O objetivo desta revisão integrativa foi verificar os instrumentos empregados para mensurar a autoeficácia relacionada ao desempenho esportivo e identificar suas propriedades psicométricas. Buscaram-se artigos nas bases de dados Eric, Scopus e APA (Psycnet), Scielo ScienceDirect e Pubmed com os descritores self-efficacy, sports, performance. Dos 13 estudos selecionados para análise, constatou-se que a maioria propôs instrumentos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
0
9
0
5
Order By: Relevance
“…Verificou-se que 64% (dezesseis) dos artigos selecionados neste estudo de revisão apresentaram ao menos os itens que compunham o instrumento, sendo que 20% (cinco) apresentaram os instrumentos completos 43,44,49,56,57 . Este dado é, de certa forma, satisfatório, tendo em vista que em um estudo semelhante realizado por Machado et al 67 , o qual revisou estudos sobre instrumentos de medida da autoeficácia esportiva, nenhum dos artigos apresentou o instrumento utilizado na íntegra, sendo que alguns fizeram, apenas, menção de itens pertencentes ao instrumento.…”
Section: Resultsunclassified
“…Verificou-se que 64% (dezesseis) dos artigos selecionados neste estudo de revisão apresentaram ao menos os itens que compunham o instrumento, sendo que 20% (cinco) apresentaram os instrumentos completos 43,44,49,56,57 . Este dado é, de certa forma, satisfatório, tendo em vista que em um estudo semelhante realizado por Machado et al 67 , o qual revisou estudos sobre instrumentos de medida da autoeficácia esportiva, nenhum dos artigos apresentou o instrumento utilizado na íntegra, sendo que alguns fizeram, apenas, menção de itens pertencentes ao instrumento.…”
Section: Resultsunclassified
“…Two studies reported the Cronbach's alpha values, and these values are specific to the studies in question (Zetou et al, 2012), whereas no values were included from the validation study of the instrument used (Blecharz et al, 2014). This is a recurrent factor in several studies, and the authors end up presenting only the validity of the data obtained with the measurement instrument specifically in their study, but not the value originally obtained in the study on the elaboration and validation of the instrument, thus affecting reproducibility and comparisons between studies (Machado et al, 2014).…”
Section: Number Of Paper Identificationmentioning
confidence: 99%
“…Since the first article published by Bandura on self-efficacy in 1977 within the framework of social cognitive theory, there has been great acceptance of this construct in different contexts, including the sport context. Specifically, although the self-efficacy construct was proposed by Bandura (1977) to address the treatment of anxiety in clinical psychology, selfefficacy has been an important research topic in the sport context (Balaguer, Escarti, & Villamarín, 1995;Machado, Paes, Berbetz, & Stefanello, 2014) with athletes from different competitive levels and modalities, such as freediving (Baretta, Greco, & Steca, 2017), taekwondo (Estevan, Álvarez, & Castillo, 2016), basketball (Lázaro & Villamarín, 1993; Olmedilla, Sainz de Baranda, & Gómez, 2009;Ortega, Olmedilla, & Cárdenas, 2007), golf (Irazusta & Arruza, 2006;Rodriguez, López, Gómez, & Rodríguez, 2015), tennis (Gónzalez, 2017), and football (García-Naveira, 2018;Leo, García-Calvo, Sanchez-Miguel, & Parejo, 2008; Leo, García-Calvo, Sánchez-Miguel, & de la Vega, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing body of scientific literature underscoring the significance of selfefficacy in sports performance, measurement of efficacy beliefs among athletes has been inconsistent in quality, making it essential to carefully employ optimal assessment approaches to evaluate athletes' self-efficacy (Feltz et al, 2008). Sport specificity (e.g., for volleyball self-efficacy) has not been well addressed in past studies (Machado et al, 2014). Consequently, research analyses in this field have often employed less than ideal assessment tools that are not tailored to the unique characteristics of the sport in question (Gilson et al, 2012;Luszczynska et al, 2005;Theodorakis, 1996;Zetou et al, 2008Zetou et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Grunnell et al (2014) called for improvements in the measurement instruments used in this discipline. In addition, other past researchers have encouraged a search for validity evidence of new instruments that measure self-efficacy in different languages and population groups (Cassepp-Borges et al, 2010), since most past studies on self-efficacy were carried out in English-speaking countries, ignoring other cultural contexts (Machado et al, 2014).…”
Section: Introductionmentioning
confidence: 99%